Occurrence of venlafaxine, other antidepressants and selected metabolites in the Rhine catchment in the face of climate change. (January 2015) - Schlüsener, Michael P.; Hardenbicker, Paulin; Nilson, Enno; Schulz, Manoj; Viergutz, Carsten; Ternes, Thomas A.
Abstract: Fate and occurrence of 4 selective serotonin reuptake inhibitors, one serotonin-noradrenergic reuptake inhibitor and one noradrenergic-dopamineric reuptake inhibitor and their human metabolites were determined in a German municipal wastewater treatment plant as well as in the Rhine River and selected tributaries. The enantiomeric fractions of venlafaxine and its metabolites were not altered during wastewater treatment and were similar in all river samples underlining that no appreciable biodegradation occurs. In the Rhine catchment area highest concentrations were detected for venlafaxine, citalopram and their human metabolites. Projected future climate change would lead to an increased portion of treated wastewater in rivers due to reduced discharges during low flow situations by the end of the 21st century. However, the effect of climate change on the pattern and concentrations of antidepressants is predicted to be of minor importance in comparison to altered consumption quantities caused by demographic developments and changes in life styles. Highlights: Occurence and fate of antidepressants in the Rhine catchment area. The most dominant antidepressants were venlafaxine, citalopram and their metabolites. Venlafaxine and its metabolites were hardly removed in WWTPs. Projected climate change would lead to an increased portion of wastewater in rivers. Estimation the fate of antidepressants during different climate change scenarios. Abstract : The fate of the antidepressants was determined in the Rhine catchment area with regard to the influence of climate change on the concentration of antidepressants in rivers.